(untitled) (Scientific journal of the Fergana State University, 2023)
The article notes that the ruins of the ancient city in Fergana Valley, the ceramics found in the tombs, can provide a lot of material on social, economic and cultural relations with neighboring areas, in addition to identifying the Bronze, Early Iron and Ancient cultures.